RIM1 and RIM2 redundantly determine Ca(2+) channel density and readily releasable pool size at a large hindbrain synapse - Han, Yunyun (J Neurophysiol, 2014)
The localization and density of voltage-gated Ca(2+) channels at active zones are essential for the amount and kinetics of transmitter release at synapses. RIM proteins are scaffolding proteins at the active zone that bind to several other presynaptic proteins, including voltage-gated Ca(2+) channel α-subunits. The long isoforms of RIM proteins, which contain NH(2)-terminal Rab3- and Munc13-interacting domains, as well as a central PDZ domain and two COOH-terminal C2 domains, are encoded by two genes, Rim1 and Rim2. Here, we used the ideal accessibility of the large calyx of Held synapse for direct presynaptic electrophysiology to investigate whether the two Rim genes have redundant, or separate, functions in determining the presynaptic Ca(2+) channel density, and the size of a readily releasable vesicle pool (RRP). Quantitative PCR showed that cochlear nucleus neurons, which include calyx of Held generating neurons, express both RIM1 and RIM2. Conditional genetic inactivation of RIM2 at the calyx of Held led to a subtle reduction in presynaptic Ca(2+) current density, whereas deletion of RIM1 was ineffective. The release efficiency of brief presynaptic Ca(2+) “tail” currents and the RRP were unaffected in conditional single RIM1 and RIM2 knockout (KO) mice, whereas both parameters were strongly reduced in RIM1/2 double KO mice. Thus, despite a somewhat more decisive role for RIM2 in determining presynaptic Ca(2+) channel density, RIM1 and RIM2 can overall replace each other's presynaptic functions at a large relay synapse in the hindbrain, the calyx of Held.